Quantifying polyphosphate energy for modelling of polyphosphate accumulating organisms behaviour in anaerobic digestors - Chen-Chen, Cornelius (Department of Civil Engineering, 2025)
This study investigated the behaviour of polyphosphate accumulating organisms (PAOs) in linked activated sludge-anaerobic digestion (AS-AD) systems, with particular focus on quantifying polyphosphate (PolyP) energy and its role in PAO metabolism. The study was motivated by observed discrepancies between theoretical predictions and experimental observations in AD systems treating phosphorus-rich waste activated sludge, particularly regarding pH predictions and mineral precipitation patterns. The research employed a University of Cape Town membrane bioreactor activated sludge (UCT MBR AS) system to cultivate an enriched PAO culture. This approach successfully achieved high PAO concentrations, enabling detailed investigation of PAO metabolism and stored PolyP levels. The experimental methodology combined operational data from both AS and AD systems with comprehensive chemical analyses and mass balance validations. Two conceptual models were evaluated for PolyP release stoichiometry in AD: one incorporating PHB formation with PolyP energy utilization, and another assuming direct PolyP release without PHB formation. The comparison aimed to elucidate energy transfer mechanisms between AS and AD systems. The research demonstrated successful cultivation of an enhanced PAO culture in the AS system, achieving significant phosphorus cycling capabilities and robust metabolic activity. The investigation of PAO behaviour in AD environments revealed complex interactions between biological processes and chemical equilibria. The experimental results provided strong evidence supporting the hypothesis that PAOs utilize stored PolyP energy for PHB formation in AD environments. This was particularly evident in pH and alkalinity measurements, which aligned more closely with the model incorporating PHB formation. Significant findings included the observation of rapid PolyP release within initial digestion days, complex precipitation dynamics, and marked differences between total and dissolved metal ion concentrations. The research validated the role of PolyP as an energy carrier between AS and AD systems, while also highlighting limitations in current precipitation kinetics modelling approaches. The study's findings have important implications for understanding PAO metabolism and energy utilization in wastewater treatment processes. The research contributes to improved prediction of AD performance when treating phosphorus-rich sludge and offers insights for optimizing biological nutrient removal systems. Future research directions were identified, particularly regarding molecular-level understanding of PAO metabolism and the development of enhanced precipitation models. This investigation advances our understanding of biological phosphorus removal processes and provides practical guidance for improving wastewater treatment system design and operation. The findings support more accurate modeling approaches and highlight the importance of considering energy transfer mechanisms in linked AS-AD systems.